Novel Tl2GeX6 (X=Cl,Br) double perovskites for solar cell, optoelectronic, and thermoelectric applications: A DFT investigation - Redi Kristian Pingak; Amine Harbi; Soukaina Bouhmaidi; Albert Z. Johannes; Nikodemus U.J. Hauwali; Wahidullah Khan; Fidelis Nitti; David Tambaru; M. Moutaabbid; Larbi Setti (Chemical Physics Impact)
This study aims to investigate the structural, mechanical, optical, electronic, and thermoelectric properties of novel double perovskites Tl2GeCl6 and Tl2GeBr6. The Quantum Espresso code was employed to perform the Density Functional Theory (DFT) calculation on the perovskites’ characteristics. The results indicated that both materials exhibit chemical and structural stability, with equilibrium lattice constants of 10.08 Å and 10.55 Å for Tl2GeCl6 and Tl2GeBr6, respectively. The calculated elastic parameters and elastic moduli data also demonstrated that the new double perovskites exhibit mechanical stability while the calculated electronic band structure and the density of states using the PBE functional indicated that the materials are semiconductors with energy gap values of 0.3 eV for Tl2GeBr6 and 1.72 eV for Tl2GeCl6, respectively. Using more accurate SCAN approximation, the energy gaps were refined to 0.53 eV for Tl2GeBr6 and 2.10 eV for Tl2GeCl6. Additionally, the calculated dielectric functions, extinction coefficient and absorption coefficients of Tl2GeCl6 and Tl2GeBr6 strongly suggest the exceptional optical response of these materials. Notably, Tl2GeBr6 is estimated to have a particularly strong visible-light absorption capacity, positioning it as a promising absorber for perovskite solar cells. These findings are also supported by the low reflectivity values observed. Finally, the analysis of their thermoelectric properties revealed the excellent thermoelectric properties of Tl2GeCl6 and Tl2GeBr6, as indicated by their high figures of merit, predicted to be 0.73 and 0.68 for the respective perovskites.